Provincial distribution of unintended pregnancy and its associated factors in Sierra Leone - Augustus Osborne; Regina Mamidy Yillah; Camilla Bangura; Bright Opoku Ahinkorah (BMC Public Health)
Abstract Background Unintended pregnancy is a significant public health concern in Sierra Leone, with far-reaching consequences for both mothers and children. This issue impacts individual well-being, strains healthcare systems, and hinders socioeconomic development. This study examined the prevalence and factors associated with unintended pregnancy in Sierra Leone. Methods Data from the 2019 Sierra Leone Demographic and Health Survey was used for the study. Provincial variations in the prevalence of unintended pregnancy was presented using a spatial map. A mixed-effect multilevel binary logistic regression models was fitted to examine the factors associated with unintended pregnancy. The results were presented as adjusted odds ratios (aOR) with a 95% confidence interval (CI) and intra-cluster correlation coefficients. Results In Sierra Leone, the national prevalence of unintended pregnancy was 16.4% in 2019. Women aged 20–49 exhibit lower odds of unintended pregnancy compared to those aged 15–19, with the lowest odds found among those aged 30–34. Factors associated with decreased odds include being employed, married or cohabiting, and belonging to the Fullah tribe, while living in various provinces outside the Western area also correlates with lower odds. Conversely, women with secondary education, listened to the radio, those with more children (5+), contraceptive users, larger household sizes (six or more), and those in the middle wealth index had increased odds of unintended pregnancies. Conclusion The results from Sierra Leone indicate that various socio-economic and demographic factors significantly influence the prevalence of unintended pregnancies, suggesting critical areas for intervention. For women in the 20–49 age group, the lower odds of unintended pregnancies compared to younger women suggest that targeted educational and health initiatives could further enhance their reproductive health outcomes. The protective factors associated with employment, marital status, and tribal affiliation highlight the importance of promoting stable family structures and economic opportunities. Also, women living in the Eastern, Northwestern, Northern, and Southern provinces, the results imply a need for province-specific interventions. These areas may require tailored outreach programs that address cultural and socio-economic barriers to contraceptive use and reproductive health education. The increased odds linked to secondary education, listening to radio, those with more children, contraceptive users, and larger household sizes suggest that educational initiatives should also address family planning and reproductive health. A focused approach that considers the unique needs of these women could lead to more effective strategies in reducing unintended pregnancies in Sierra Leone.